FUNGSI BUKTI AUDIT DALAM TINDAK PIDANA KORUPSI - Yulianto Dirdjosumarto (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2016)
ABSTRACT : In criminal law, in corruption case, in forensic accounting, and in auditing (investigative auditing), evidence has important role. As we know that auditing can be regarded as a systematic process to obtain and evaluate evidence in frame of comparing condition with specific criteria. Evidence in common must be admissible and relevant so that it can properly be received by a court as a matter of law or it relates to the facts. Based on article 184 (1) KUHAP, the tools of evidence include : (a). testimony of witness; (b). expert opinion; (c). written documents; (d). guidances; and (e). confessions evidence. Arens et.al. (2011 : 158) classify audit evidence into 8 categories such as (a). physical examination; (b). confirmation evidence; (c). documentation evidence; (d). analytical procedures; (e). inquiry; (f). recalculation; (g). reperformance; and (h). observation. In relation to the KUHAP, audit evidences should be used as references to the tools of evidence in KUHAP. The roles of audit evidences as follows : (1). physical examination can be used as testimony of witness and confessions evidence; (2). confirmation evidence can be used as written documents, testimony evidence and confessions evidence; (3). documentation evidence can be used as written documents, testimony of witness and expert opinion; (4). analytical procedures can be developed as expert opinion; (5). inquiry can be used as testimony of witness and confessions evidence; (6). recalculation can be developed as written documents; (7). reperformance can be developed as written documents; and (8). observation due to obtaining from presumption, can not be used as legal evidence.